Process optimization of cabinet dried mango (Mangifera indica L. cv. Pico) slices using response surface methodology - Ametin, Janine T.; Rustia, Abigail S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
This study aimed to optimize the process parameters of the cabinet drying of mango (Mangifera indica L. cv. Pico) slices using response surface methodology. Specifically, this study (1) evaluated the effect of stage of ripeness on the quality and consumer acceptability of cabinet-dried mango slices; and (2) established and verified the optimized process parameters for cabinet drying on the quality of Pico mango slices that includes drying temperature (°C) and loading capacity (g/cm2). The appropriate stage of ripeness used throughout the phases of the study was Pico mango at 5 days after harvest (105 days after flower induction (DAFI) + 5 days after harvest) with the highest overall acceptability of 6.81 -"like slightly". Statistical models generated described the effects of loading capacity on drying time (min), water activity (aw), color (L*, a*, b* values, % moisture content (dry basis), and consumer acceptability in terms of appearance, color, aroma, texture, flavor and overall acceptability of cabinet dried Pico mango slices. The established optimum cabinet drying parameters for cabinet dried Pico mango slices, having a desirability of 0.951, was 75.0 °C with loading capacity of 0.45g/cm2. Verification experiments showed the reliability of the predictive models generated and the validity of the optimized process parameters at significance level of α=0.05.
Thesis Classification: P
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Keywords: Mango -- Philippines; Dried mango